2008
DOI: 10.1007/s10096-008-0653-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of Salmonella enterica subspecies enterica serovar 9,12:l,v:- strains from Bulgaria, Denmark, and the United States

Abstract: In 2006, Salmonella enterica serovar I 9,12:l,v:- emerged in Bulgaria. The aim of this study was to characterize Salmonella serovar I 9,12:l,v:- isolates from Bulgaria, Denmark, and the United States. We compared isolates of Salmonella I 9,12:l,v:- and diphasic serovars with similar antigenic formulas by pulsed-field gel electrophoresis (PFGE) and antimicrobial susceptibility. The phase 2 flagellin gene (fljB) was also sequenced for selected isolates. By PFGE, the Salmonella I 9,12:l,v:- isolates from Bulgaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As a result, various molecular methods have been proposed as potential alternatives to serotyping for subdividing Salmonella (and other microbes) [15], [16], ranging from PFGE (Pulsed-Field Gel Electrophoresis) [17], [18] through to MLVA (MultiLocus Variable number of tandem repeats Analysis) [19], [20]. These methods are possibly useful for recognizing a common source of microorganisms from a single outbreak [21], but they are inappropriate for reliable assignments of isolates to one of the 2,500 S. enterica serovars. Still other attempts have been made to develop DNA-sequence based equivalents of serotyping [22][26], including the detection of particular single nucleotide polymorphisms (SNPs) within flagellar antigens [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, various molecular methods have been proposed as potential alternatives to serotyping for subdividing Salmonella (and other microbes) [15], [16], ranging from PFGE (Pulsed-Field Gel Electrophoresis) [17], [18] through to MLVA (MultiLocus Variable number of tandem repeats Analysis) [19], [20]. These methods are possibly useful for recognizing a common source of microorganisms from a single outbreak [21], but they are inappropriate for reliable assignments of isolates to one of the 2,500 S. enterica serovars. Still other attempts have been made to develop DNA-sequence based equivalents of serotyping [22][26], including the detection of particular single nucleotide polymorphisms (SNPs) within flagellar antigens [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cattle faeces showed more diversity in serovars of Salmonella spp., than has been reported in other studies (Petrov et al . ; Schneider et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the previously unsequenced serovar 9,12:l,v:Ϫ has the highest invasive index among all NTS serovars in Israel and is associated with multiple salmonellosis clusters (Table 1), which prompted us to further characterize this serovar on the genetic level. This monophasic serovar, which has recently emerged in Bulgaria, Denmark, and the United States (24), was thought to have evolved from a strain of Salmonella enterica serovar Goettingen (9,12:l,v: e,n,z15) (25), and the two serovars share the multilocus sequence type (MLST) 20 (http://mlst.warwick.ac.uk/mlst/dbs/Senterica).…”
Section: Characterizationmentioning
confidence: 99%